Fresno County Bar Association Wilkin Judges Dinner at Crossland's Barn - Watkins, Howard::::::::: (1984)
Patty Cartan, Debra Kazanjian, Harry Papadakis; Victor Papadakis and Gary Austin in backgroundxxxx